1997
DOI: 10.1016/s0893-133x(97)00086-9
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Premenstrual Syndrome Have Reduced Sensitivity to Midazolam Compared to Control Subjects

Abstract: Premenstrual syndrome (PMS) depends on gonadal hormones produced by the corpus luteum. Given the facilitory actions on GABAergic inhibitory neurotransmission exerted by certain progesterone metabolites, further studies on the GABAA receptor system in premenstrual syndrome are warranted. This study evaluated the benzodiazepine sensitivity in PMS patients and control subjects, using saccadic eye velocity (SEV) and visual analogue ratings of sedation as dependent measures. PMS patients displayed a significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 38 publications
11
77
0
3
Order By: Relevance
“…Further, this anxiogenic effect of flumazenil was not observed in the δ knockout mouse, suggesting that α4βδ GABAR mediate this atypical effect of the BDZ antagonist. Both the BDZ insensitivity (Sundstrom et al 1997) and anxiogenic effect of flumazenil (Le Melledo et al 2000) have been reported for women with PMDD, suggesting an additional comparison with the THP withdrawal model in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…Further, this anxiogenic effect of flumazenil was not observed in the δ knockout mouse, suggesting that α4βδ GABAR mediate this atypical effect of the BDZ antagonist. Both the BDZ insensitivity (Sundstrom et al 1997) and anxiogenic effect of flumazenil (Le Melledo et al 2000) have been reported for women with PMDD, suggesting an additional comparison with the THP withdrawal model in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…PMDD women also report more traumatic life stress, including sexual and physical abuse histories (Paddison et al, 1990;Golding & Taylor, 1996Girdler et al, 2003Girdler et al, , 2007. Since allopregnanolone is stress responsive, at least in animal models (Purdy et al, 1991;Barbaccia et al, 1996Barbaccia et al, , 1997, greater allostatic load in PMDD resulting from more severe life stress could contribute to the elevated allopregnanolone concentrations that we have seen in PMDD women (Girdler et al, 2001) and result in the documented alterations in GABA A receptor function in PMDD (Sundstrom et al, 1997a(Sundstrom et al, , 1997b(Sundstrom et al, , 1998, including alterations in the agonism properties of the GABA A receptor as animal models (Smith et al, 2006) and human studies of PMDD suggest (Le Melledo et al, 2000). This could then explain the seemingly paradoxical association between increasing allopregnanolone concentrations in the luteal phase and increased dysphoric mood states in PMDD.…”
Section: Allopregnanolone Responses To Stress In Pmddmentioning
confidence: 83%
“…Behaviorally, PMDD women also generally report less sedation in response to the i.v. benzodiazepines (Sundstrom et al, 1997a(Sundstrom et al, , 1997b. The clinical significance of these results comes from their findings that when PMDD women are divided into lower versus higher symptom severity groups, the more severe PMDD symptom groups respond with less of a reduction in SEV (Sundstrom et al, 1997b(Sundstrom et al, , 1998 and with lower sedation ratings (Sundstrom et al, 1998) in response to benzodiazepines.…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddmentioning
confidence: 98%
See 2 more Smart Citations